Clinical predictors of pulmonary tuberculosis among South African adults with HIV. (March 2022) - Mendelsohn, Simon C.; Fiore-Gartland, Andrew; Awany, Denis; Mulenga, Humphrey; Mbandi, Stanley Kimbung; Tameris, Michèle; Walzl, Gerhard; Naidoo, Kogieleum; Churchyard, Gavin; Scriba, Thomas J.; Hatherill, Mark; ,
Summary: Background: Tuberculosis (TB) clinical prediction rules rely on presence of symptoms, however many undiagnosed cases in the community are asymptomatic. This study aimed to explore the utility of clinical factors in predicting TB among people with HIV not seeking care. Methods: Baseline data were analysed from an observational cohort of ambulant adults with HIV in South Africa. Participants were tested for Mycobacterium tuberculosis (Mtb) sensitisation (interferon-γ release assay, IGRA) and microbiologically-confirmed prevalent pulmonary TB disease at baseline, and actively surveilled for incident TB through 15 months. Multivariable LASSO regression with post-selection inference was used to test associations with Mtb sensitisation and TB disease. Findings: Between March 22, 2017, and May 15, 2018, 861 participants were enrolled; Among 851 participants included in the analysis, 94·5% were asymptomatic and 45·9% sensitised to Mtb. TB prevalence was 2·0% at baseline and incidence 2·3/100 person-years through 15 months follow-up. Study site was associated with baseline Mtb sensitisation ( p  < 0·001), prevalent ( p  < 0·001), and incident TB disease ( p  = 0·037). Independent of site, higher CD4 counts (per 50 cells/mm 3, aOR 1·48, 95%CI 1·12–1·77, p  = 0·006) were associated with increased IGRA positivity, and participants without TB disease (aOR 0·80, 95%CI 0·69–0·94, p  = 0·006) had reduced IGRA positivity; no variables were independently associated with prevalent TB. Mixed ancestry (aHR 1·49, 95%CI 1·30–>1000, p  = 0·005) and antiretroviral initiation (aHR 1·48, 95%CI 1·01–929·93, p  = 0·023) were independently associated with incident TB. Models incorporating clinical features alone performed poorly in diagnosing prevalent (AUC 0·65, 95%CI 0·44–0·85) or predicting progression to incident (0·67, 0·46–0·88) TB. Interpretation: CD4 count and antiretroviral initiation, proxies for immune status and HIV stage, were associated with Mtb sensitisation and TB disease. Inadequate performance of clinical prediction models may reflect predominantly subclinical disease diagnosed in this setting and unmeasured local site factors affecting transmission and progression. Funding: The CORTIS-HR study was funded by the Bill & Melinda Gates Foundation (OPP1151915) and by the Strategic Health Innovation Partnerships Unit of the South African Medical Research Council with funds received from the South African Department of Science and Technology. The regulatory sponsor was the University of Cape Town.